From skulls to faces: unveiling the secrets of identity with 3D facial reconstruction - Atikah Mohd Nasir,; Han Jia Siew,; Khairul Osman,; Nur Mahiza Md Isa,; Noor Hazfalinda Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2025)
3D facial reconstruction is a technique in forensic science used to create images of unidentified individuals based on skeletal remains, aiding investigations and forming part of forensic anthropology. This technique utilises computer software and anatomical data to create a digital model depicting a likeness of the individual’s face. By employing this technology, forensic investigators can obtain valuable facial characteristics that aid in identification, such as ethnicity, age, and potential distinguishing features. This article will further discuss the development of 2D to 3D facial reconstruction and its working principles. Additionally, the impact of cosmetic surgery on the accuracy of reconstruction will also be explored. Lastly, the challenges and limitations of 3D facial reconstruction will be reviewed.